Implementação, avaliação, manutenção e reestruturação do serviço de referência das bibliotecas universitárias brasileiras à luz das diretrizes da American Library Association - Jorge Santa Anna (2023)
The Reference Service in university libraries constitutes the main focus of this thesis and the research environment is Brazilian university libraries. The need for constant improvement and improvement of this service poses problems in identifying whether it complies with the guidelines proposed by the American Library Association. The objective of the research is to correlate management actions regarding the implementation, evaluation, maintenance and restructuring of the Reference Service of Brazilian university libraries in light of the guidelines of the American Library Association. The study reflects on the development and concepts of the Reference Service in university libraries; describes the elements that characterize this service from the point of view of its implementation, evaluation, maintenance and restructuring; explores the role of Ranganathan's five laws as a guiding principle for access to information in libraries and the implementation of the Reference Service; carries out a diagnosis of the Reference Service of the mentioned libraries; and identifies the challenges faced in managing this service and the advances achieved through the actions implemented. The study is characterized as descriptive and exploratory, with the application of bibliographic, documentary and field research, whose sample corresponded to 109 university libraries in Brazil (federal and state). As data collection instruments, the form and structured questionnaire were applied, with open and closed questions, and, for data analysis, content analysis was used. From the results, it became clear that the scarcity of human resources (insufficient number of members to make up the reference team) and the lack of integration between the team and the institution's sectors constitute recurring challenges. The implementation of training/qualification, the use of digital resources (especially social networks) and the carrying out of cultural actions to encourage the use of the service were considered the main advances. It was observed that most of the challenges are largely related to the human factor, that is, human resources, which are essential for forming a trained team to work in the Reference Service. Research assistance constitutes a basic component of the service and, together with training and cultural actions, reinforce its educational characteristic, with these elements benefiting from the use of different technologies, which will seek to increase harmony between the library and its audiences. To ensure the expansion of the Reference Service, the importance of taking advantage of technological resources was highlighted, which are necessary to create communication channels in their various formats, whether synchronous (telephone, chat, web conferences, among others) or asynchronous (and -email, social networks, web form, among others). It was concluded that the Reference Service is characterized as heterogeneous between one institution and another and there are efforts to expand and continually improve the service offered to users, with 20 recommendations being made to strengthen the service. The recommendation is that the team be distributed across three work fronts, with a view to the diversification of activities that permeate this service, namely: research support, training and promotion of the service.